(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2015)
This study evaluated the variation of craving and heart rate during exposure in hospitalized crack dependents. Experimental study that had random sample of crack addicts admitted. The subjects were divided into an experimental group (n=30) to whom were presented crack related photographs and the control group (n=30) who saw landscapes (neutral) photos. During the exposure time heart rate, craving and trust were controlled. It was observed that the experimental stimulus has had a significant effect on the variability of craving (p=0,006) and heart rate (p=0,008), this phenomenon did not occur for trust (p=0,983). The correlation between craving and heart rate was significant and of low intensity (r = 0.347; p